Ensino de botânica: percepções discentes sobre o estudo de diversidade vegetal no ensino superior - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The Teaching of Botany in undergraduate courses is still seen with theoretical methodologies, little contextualized with reality, often without presenting attractions in classes that contribute to the reduction of Botanical Imperception. Based on these concerns about Teaching Botany, this study sought to analyze the perceptions of students of the Natural Sciences Course in relation to EB, during their higher education. Based on a qualitative and quantitative research. For this, three objectives were listed, where the first was to carry out a search in the CAPES database of dissertations and theses, on works aimed at EB in several PPG in Education in the country, 11 works were found between the years 2016 to 2020, in which most of these works were developed in the southeast region of the country compared to other regions of the country that were in low production on this subject, which characterizes a decrease in the development of these researches. In the second objective, we sought to verify the conceptions of freshman and finalist students of the LCN course, about which areas of Natural Sciences they were most interested in high school, this research for freshmen, as for the finalists, the perceptions about the components related to Botany offered in the course, it was noticed here that during high school Biology was the area of greatest interest and also continues to be in Higher Education, the freshmen intend that the components linked to Botany can be more in-depth during the course, for graduates, the positive points are in the interdisciplinarity that the components bring and their weaknesses are in the low workload and also in the impracticability of faceto-face classes during the pandemic period. The third objective was to investigate the potential of experimental practical activities in the components of Plant Diversity, if it was noticed that the students envision that the activities applied in the classes should be repeated in basic education, as well as suggest further in-depth discussions about Botany in the course. Therefore, it is necessary that research with this theme can be further developed and applied, aiming at greater knowledge, dissemination and reduction of Botanical Imperception.
Botany teaching: student perceptions about the study of plant diversity in higher education
Keywords: Botânica; Plant Diversity; University Education; Botany; Natural Sciences; Diversidade vegetal; Ensino superior; Ensino superior; Ciências da natureza; CIENCIAS HUMANAS